Pengembangan Video Pembelajaran Animasi untuk Meningkatkan Keterampilan Menulis Teks Naratif di Kelas IV Sekolah Dasar - Triningsih, Renatalia; Yarmi, Gusti; Nurhasanah, Nina (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to determine the feasibility and effectiveness of animated learning video media in improving narrative text writing skills among fourth-grade elementary school students. The background of this research is that writing skills are often regarded as the final skill in the hierarchy of language skills taught in Indonesian language lessons. Writing is the last skill developed after reading, listening, and speaking. Narrative text writing is one of the essential competencies that students must master. Therefore, alternative methods are needed to enhance the teaching of Indonesian language skills, particularly narrative text writing. This necessity drives researchers to develop animated learning videos to make the learning process more enjoyable. The development model employed in this study is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The findings reveal a significant improvement in narrative text writing skills following trials conducted with fourth-grade elementary school students. Thus, this media can be considered an effective alternative for teaching the Indonesian language. These findings affirm that animated learning videos are a potent tool for enhancing narrative text writing skills in elementary education.